2019
DOI: 10.2320/matertrans.mf201935
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Severely Deformed Pure and Single-Phase Materials

Abstract: The significant and complex effect of plastic deformation on corrosion behavior involves changes in not only dislocation density but also other metallurgical factors such as grain size, texture, chemical inhomogeneity, phase transformation and residual stress. With the advent of severe plastic deformation (SPD), the effect of plastic deformation on corrosion in the ultrahigh strain range is becoming an important issue. However, our understanding of corrosion properties of SPD materials lags far behind than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 145 publications
(257 reference statements)
4
32
0
Order By: Relevance
“…[70] The nonequilibrium grain boundaries demonstrate almost double the energy of equilibrium ones. [33,75] We propose grain boundary equilibration as the probable reason for the enhanced corrosion resistance of nano Ti after short-term annealing. However, the probable enhanced potential difference between the grain boundaries and grain interiors, which are virtually free of dislocations, may be the reason for slightly lower corrosion resistance after extended heat treatment.…”
Section: Low Temperature Annealing-better Ductilitymentioning
confidence: 90%
See 1 more Smart Citation
“…[70] The nonequilibrium grain boundaries demonstrate almost double the energy of equilibrium ones. [33,75] We propose grain boundary equilibration as the probable reason for the enhanced corrosion resistance of nano Ti after short-term annealing. However, the probable enhanced potential difference between the grain boundaries and grain interiors, which are virtually free of dislocations, may be the reason for slightly lower corrosion resistance after extended heat treatment.…”
Section: Low Temperature Annealing-better Ductilitymentioning
confidence: 90%
“…[31] UFG/nano Ti products obtained by large plastic deformation methods demonstrate both superior mechanical properties and higher corrosion resistance compared with microcrystalline CP-Ti. [32,33] Mott-Schottky tests demonstrated that the passive layer formed on the nano Ti surface in simulated physiological conditions is less defective than micro CP-Ti. [7] Moreover, the huge number of structural defects in nano and UFG Ti is expected to accelerate the passivation (Figure 2) and repassivation process after damage to the oxide layer, which may be induced by tribocorrosion phenomena.…”
Section: Grain Refinement To the Nanoscale-an Alternative To Ti6al4vmentioning
confidence: 98%
“…In fact, the whole surface of the sample gradually becomes covered by corrosion products which shows a more general type of corrosion after long immersion times. A pseudouniform type of corrosion has been suggested in ultrafine‐grained materials [ 28,29 ] and earlier reports showed essentially uniform corrosion in ultrafine‐grained pure Mg. [ 3,4 ] It is interesting to note that the addition of HA fails to change this behavior despite the potential for forming galvanic cells in a composite.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, the new concept of thermal insulation rolling table equipment and edge crack suppression for the magnesium alloy is put forward in this paper. Combined with the study of cathodic protection, the method realizes to suppress edge crack and hydrogen corrosion [44,45] in rolling process of the magnesium alloy plate and effectively improve the forming quality of the magnesium plate [46].…”
Section: Introductionmentioning
confidence: 99%